2021
DOI: 10.1017/s0269964820000704
|View full text |Cite
|
Sign up to set email alerts
|

On Markovian Queues With Single Working Vacation and Bernoulli Interruptions

Abstract: This paper considers the customers’ equilibrium and socially optimal joining–balking behavior in a single-server Markovian queue with a single working vacation and Bernoulli interruptions. The model is motivated by practical service systems where the service rate can be adjusted according to whether or not the system is empty. Specifically, we focus on a single-server queue in which the server's service rate is reduced from a regular to a lower one when the system becomes empty. This lower rate period is calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The time away from the primary service center is called vacation and can be attributed to several factors. For a comprehensive and complete review of vacation queuing systems, we refer the readers to Doshi [9], Takagi [10], Tian and Zhang [11], Ke et al [12] and Chandrasekaran et al [13], who conducted a survey describing the latest research on the working vacation queueing system. Recently, Panta et al [14] surveyed vacation queuing models.…”
Section: Introductionmentioning
confidence: 99%
“…The time away from the primary service center is called vacation and can be attributed to several factors. For a comprehensive and complete review of vacation queuing systems, we refer the readers to Doshi [9], Takagi [10], Tian and Zhang [11], Ke et al [12] and Chandrasekaran et al [13], who conducted a survey describing the latest research on the working vacation queueing system. Recently, Panta et al [14] surveyed vacation queuing models.…”
Section: Introductionmentioning
confidence: 99%
“…Tese queueing models are often used in computer systems and telecommunication networks. General models, methods, results, examples, and applications of retrial queues can be found in Artalejo and Gómez-Corral [1], Tian et al [2]. In recent years, Phung-Duc [3] used retrial queues to model cloud computing systems and gave the steady-state probabilities of the systems.…”
Section: Introductionmentioning
confidence: 99%